Modeling and simulation of parallel adaptive divide-and-conquer algorithms - Barros, Fernando J. (The Journal of supercomputing, 2008)
Conventional modeling and simulation formalisms only give support to the representation of model behavior, providing no constructs for describing changes in model structure. However, some systems are better modeled by self-reconfigurable formalisms. We have developed the Discrete Flow System Specification (DFSS) to exploit dynamic structure, component-based and hierarchical model construction. Due to structural similarity, dynamic self-configuring DFSS models offer a good description of systems, like adaptive algorithms and reconfigurable computer architectures. In this paper, we present the modeling and simulation of a parallel adaptive divide-and-conquer integration algorithm in the C aos T alk modeling and simulation framework, a realization of the DFSS formalism.